Antioxidant Protection of Donor Packed Red Blood Cells using Mexidol - D.V. Gavryuchenkov; I.V. Fedoseykin; V.E. Kosachev; V.A. Shapovalova; E.N. Dinov; Y.E. Dinova; I.A. Nikiforov; A.G. Merkin (Journal of Antioxidant Activity, 2018)
The current research shows the possibility of long-term conservation of the erythrocytes an-tioxidant activity in the process of donor packed red blood cells while introducing mexidol to the hemoconservant glugicir composition.
Keywords: hemoconservants